Occurence, quantification and adhesion profile of Listeria sp. isolated from slided ham - Ereno Tadielo, Leonardo; ., Luciano dos Santos Bersot (Pubvet, 2022)
The aim of this study was to evaluate the effect of the local slicing of hams, industry (IND) versus retail (VAR) on presence and quantification of Listeria monocytogenes and lactic acid bacteria during the shelf life. 240 samples were collected, from slicing by IND (n = 120) and VAR (n = 120) from three commercial brands from four establishments located in the state of Paraná, Brazil. In these samples, the research and quantification of L. monocytogenes and Lactic Acid Bacteria (BAL) were carried out, where half of the samples were analyzed on the first day of validity (T1) and the other, stored at 7º C and analyzed on the last day of validity (T2). The adhesion capacity of Listeria sp. isolates was also determined. The presence of Listeria sp. and L. monocytogenes in samples from IND, both in T1 and T2. However, 11.67% of the samples (n = 14) from the VAR presented Listeria sp. (T1 + T2). The BAL count increased at T2 when compared to T1, both in IND and VAR products. Regarding the adhesion capacity, 83.2% (n = 119) of the isolates of Listeria sp. were non-adherent and 16.8% (n = 24) showed poor adhesion capacity on polystyrene surface. Thus, the slicing carried out by the retail trade proved to be inefficient for controlling the occurrence and multiplication of Listeria sp., Where this contamination may come from the ability to form biofilms.
Keywords: Lactic acid bacteria; contamination; retail business; slicing ready-to-eat